Analisis Implementasi Temperature Screening Contactless berbasis Internet Of Things (IOT) Menggunakan Protokol Message Queue Telemetry Transport (MQTT) - Unang Achlison; Khoirur Rozikin; Fujiama Diapoldo (STEKOM PRESS, 2021)
Remote temperature monitoring is needed in hazardous area conditions or fast data retrieval is needed without being limited by distance. This condition can be overcome by monitoring and measuring the temperature from a remote location using internet technology that is currently developing, namely the Internet of things. There are many implementations of remote temperature monitoring systems, but the measurement results of these sensors sometimes have very significant differences even for measuring the temperature of the same object. This study aims to analyze the implementation of an effective and efficient remote temperature monitoring system. The temperature measurement process uses the LM35 and MLX 90614 sensors based on Internet of things technology using the Message Queue Telemetry Transport (MQTT) protocol. After obtaining the results of temperature measurements using different sensors, the measurement results are analyzed and compared with standard temperature measuring instruments to obtain an effective and efficient implementation. Based on the analysis, the results of temperature measurements using the MLX 90614 sensor are effective and efficient sensors.